A framework for ICT diffusion in public secondary schools in Kenya: case of Thika Municipality - Phinehas, John Kirimi (Strathmore University, 2013)
ICT diffusion in public secondary schools in Thika Municipality is still at infancy stage and already faces several challenges that may undermine the various initiatives undertaken by government and the private sector to promote the use of computers in schools. Based on literature and other research, this may be attributed to the fact that no framework for proper ICT diffusion in public secondary schools exists. Furthermore, most integration cases are done at random with no systematic approach based on existing frameworks or geared towards the actual context in the schools concerned. The study aimed at determining ICT usage level, barriers and ICT infrastructure established in the public secondary schools in Thika Municipality. Research findings revealed that ICT was very vital in teaching, learning and administration in the studied schools. A stratified and clustered random sample size of 20 teachers and 36 students from a target population of 236 teachers and 3252 students respectively. Questionnaires and In-depth interviews in students and teachers focus groups were used for the empirical research. The study is likely to provide school administrators, managers, teachers and students the way forward in ICT adoption strategies for pedagogical and administrative purposes. ICT diffusion in schools framework with the components of learning management system, ICT literacy development, ICT policies and planning, ICT curriculum and assessment was developed with an implementation checklist. The implementation would be introduced gradually through ICT advancement levels of exploration, application, assimilation and transformation. The research concluded that the level of ICT usage was generally good, ICT infrastructure was available but inadequate and existence of ICT usage barriers such as exams pressure and limited technical support.
To Strathmore University as a Dissertation for the Degree of Master of Science in Computer Based Information Systems
Keywords: ICT diffusion; Public secondary schools; Thika Municipality; Kenya